In vitro degradation and corrosion evaluations of plasma electrolytic oxidized Mg–Zn–Ca–Si alloys for biomedical applications - Pingping Jia; Yaokun Pan; Lang Yu; Jingtao Wang; Rui Feng; Yongxiao Wang; Xiaoying Fang; Chuanzhong Chen (Journal of Materials Research and Technology, 2023)
Biodegradable calcium phosphate (CaP) ceramic coatings were prepared on self-designed Mg-2.0Zn-0.6Ca-xSi alloys by plasma electrolytic oxidation (PEO). The effect of calcium (Ca) and silicon (Si) on alloy microstructure and coating formation and biomineralization mechanisms were discussed. The in vitro bioactivity and degradability of CaP coatings were evaluated by immersion tests in simulated body fluid (SBF) solutions and trishydroxymethyl-aminomethane hydrochloric acid (Tris-HCl) buffer, respectively. The microstructure and chemical composition of the coatings, depositions and corrosion products were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffractometer (XRD), X-ray photoelectron spectrometer (XPS) and fourier transform infrared spectrometer (FT-IR). The electrochemical corrosion behavior of alloys and coatings was investigated using the electrochemical workstation. Results showed that the shape, quantity, size and distribution of second phases can be changed by the simultaneously addition of Ca and Si in Mg–Zn–Ca–Si alloys. The Si content in Mg-2.0Zn-0.6Ca-xSi alloy should not be higher than 0.8 wt%. The microstructure of Mg-2.0Zn-0.6Ca-xSi alloys can influence the formation and growth of PEO coating by altering the spark discharge characteristics. The plasma electrolytic oxidized Mg-2.0Zn-0.6Ca-0.8Si has potential to be served as biodegradable bone implant and cardiovascular stent.